(untitled) (Revista de Medicina Clinica, 2022)
Introduction: The five-item World Health Organization wellness index (WHO-5) is among the most widely used questionnaires to assess subjective psychological well-being. Over the years, there has been much debate about the imbalance of working life and the exhaustion of the doctor, until today it has not been given so much importance. Objective: Estimate the index of emotional well-being in resident doctors Methods: Analytical, cross-sectional study with the application of the WHO-5 survey, from December 15, 2019 to May 30, 2020, variables such as age, sex, grade and specialty were taken into account, as well as the survey responses. Fisher’s exact test was applied between the degree of residence and the presence of depression or low emotional well-being, in two groups a P â‰¤0.05 was considered significant Results: 67 doctors completed the survey, the average age was 29.32 years, 52.23% Men , by specialty anesthesiology n = 23, traumatology and orthopedics 16, otorhinolaryngology n = 17, internal medicine n = 7, radiology and imaging n = 3, and general surgery n = 1. The average was (55.46%), only n = 14 (20.89%) had a score equal to or greater than 70. Conclusion: The emotional well-being index with the WHO-5 scale in training doctors was low in a large proportion, the otorhinolaryngology group did show a significant difference between the degree of residence and the presence of depression and / or a low level of well-being.